The Effects of Okra (Abelmoschus esculentus L.) Immersion Water on Changes in High-Density Lipoprotein and Low-Density Lipoprotein Levels in High Fat Diet Wistar Rat Model - Ika Setyawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. The mortality rate due to cardiovascular disease increases; one of the effects of hypercholesterolemia conditions, dyslipidemia, hypertriglyceridemia, and metabolic syndrome, not handled properly and thoroughly. This phenomenon becomes the factor that the researchers took this research topic. This study aims to determine okra (Abelmoschus esculentus L.) immersion water on an increase in high density lipoprotein (HDL) levels and decrease in LDL (low density lipoprotein) levels in high fat diet model Wistar rats. Methods. This experimental study used 30 Wistar male rats (Rattus norvegicus) divided into six groups, namely normal rats (P1), positive control (P2), standard (P3), dose 1 treatment groups (P4), dose 2 treatment groups (P5), and dose 2 treatment groups (P6). The data were collected by measuring HDL and LDL levels before and after receiving okra (Abelmoschus esculentus L.) immersion water. The data were analyzed by paired sample t-test, Wilcoxon test, ANOVA test and Kruskal-Wallis test. Results. This research showed a significant difference in the average level of HDL and LDL in all treatment groups (P4, P5, and P6) after induction of Abelmoschus esculentus L. in a high-fat diet rat model (p <0.05). Conclusion. It can be concluded that the administration of okra (Abelmoschus esculentus L.) immersion water could be used to increase HDL levels and decrease LDL levels in high fat diet model Wistar rats (p <0.05).